A Pilot Intervention Study to Improve Sexuality Outcomes in Breast Cancer Survivors - Natalia Gondim de Almeida; Tish M Knobf; Marcos Renato de Oliveira; Marina de Góes Salvetti; Mônica Oliveira Batista Oriá; Ana Virginia de Melo Fialho (Elsevier, 2020)
Objective: The main objective of the study is to assess the efficacy of the Permission, Limited information, Specific Suggestion, and sexual therapy (PLISSIT) model directly with breast cancer survivor (BCS) on sexual function and quality of life (QOL) domains. Methods: A pilot control trial was conducted comparing the PLISSIT model intervention to usual care. The intervention was delivered by two health professionals (nurse and professional sexual therapist) consisted of five sessions on counseling, genitalia anatomy, human sexual response, and sexual function. Data were collected before and 3 months after the intervention using the Female Sexual Function Index and the World Health Organization QOL-BREF questionnaire. Results: The sample consisted of 19 BCS (11 intervention, 8 controls) with a mean age of 54.5 8 years (standard deviation = 7.14) and the majority were married, Black or mixed Brazilian, received chemotherapy, radiation and/or hormonal therapy, and education varied from high school to college. There was significant improvement in physical health (P = 0.031), social relationships (P = 0.046), orgasm (P = 0.055), and pain (P = 0.049) over time and the intervention resulted in improved arousal (P = 0.038). Conclusions: The results suggest that the PLISSIT model may be an effective intervention for BCS in coping with and managing changes in sexuality and sexual function after treatment. It is important that nurses are aware of sexual intimacy concerns for BCS and integrate assessment into their nursing care.